Preliminary Numerical Experiments in Multiobjective Optimization of a Metallurgical Production Process - Filipic, B.; Tušar, T.; Laitinen, E. (Informatica)
Preliminary Numerical Experiments in Multiobjective Optimization of a Metallurgical Production Process